Silver Care: Art Therapy dengan Pendekatan Komunitas Ceria untuk Meningkatkan Interaksi Sosial Lansia - Amelia, Neta; Octaviany, Silvi; Wahyuni, Lisna Sri; Azhar, Fanisa Nur; Ariansyah, Refli; Antika, Tri; Hayati, Suci Noor (Yayasan Inspirasi El Burhani, 2026)
Introduction: The increasing elderly population in Indonesia poses challenges to psychological and social well-being. Many older adults, particularly those in social care institutions, experience loneliness, anxiety, and reduced enthusiasm for life due to limited social interaction. Observations at the UPTD Pusat Pelayanan Sosial Griya Lansia Ciparay, Bandung, revealed that residents were often passive, less expressive, and socially withdrawn. This issue led to the development of the SILVER CARE program-an innovative psychosocial intervention integrating art therapy with a cheerful community approach to stimulate creativity, interaction, and emotional balance. Objective: This community service program aimed to enhance creativity, strengthen social relationships, and improve the overall quality of life among the elderly through expressive and enjoyable group activities. Method: The intervention consisted of four structured sessions based on art therapy principles, including puzzle assembly, drawing, coloring, listening to classical music, and lavender aromatherapy. Activities promoted cooperation, self-expression, and positive interaction within a supportive atmosphere. Pre-test and post-test observations were used to evaluate social and emotional changes. Result: Findings showed notable improvements in communication, cooperation, and emotional expression. Participants became more active, confident, and enthusiastic. The program achieved 97% implementation success and produced a sustainability guidebook for partners. Conclusion: SILVER CARE effectively improved the elderly’s social, emotional, and cognitive functions. Its adaptable model offers strong potential for replication in other institutions to promote active, joyful, and meaningful aging.